Peran Indonesia Convention Exhibition terhadap Pengembangan Industri MICE di Provinsi Banten - Zairil z (Jurnal Doktor Manajemen (JDM), 2019)
The existence of exhibition halls with professional management is a major factor to boost the exhibition industry in an area. The exhibition industry is one of the supporting elements of MICE (meetings, incentives, conventions, and exhibition / events). The government has set MICE as a top five sector in bringing foreign tourists, even this sector is targeted to be able to grow up to 10% in 2019. The purpose of this paper is to analyze the growth of Indonesia Convention Exhibition (ICE) and its impact on the promotion of small and medium enterprises in Banten Province. This research uses a literature study with descriptive and explorative approaches and secondary data from Central Bureau of Statistics (BPS). It can be concluded that: (1) ICE is very potential and has a huge impact in contribution of creating jobs, increasing regional yield and income for the country, (2) With the increase of MICE events at ICE, it will attract a high number of visitors to come and be a potential market for hotel industry, event organizers (EO), travel agencies and transportation to get a decent profit. In addition, many small and medium enterprises (MSMEs) which involved in MICE industry grow their revenue such as catering services, souvenir, food and beverage sellers.